PENGARUH LINGKUNGAN SEKOLAH TERHADAP HASIL BELAJAR AKIDAH AKHLAK SISWA KELAS VII DI MTs. AL-HIDAYAH PERBAUNGAN - Masitha Kholiza Daulay; Armanilla Armanilla; Juriono Juriono (Fakultas Agama Islam Universitas Al Washliyah, 2025)
Education is a conscious effort made by every individual to acquire knowledge, change attitudes, and develop skills. Education is divided into three categories: formal, informal, and non formal, which can also be reffed to as education obtained from schools, families, and communities, among these two types of education, which are family and communities. Among these two types of education, which are family and community, school education become the formal institution that serves as the focal point and hope of parents or families and communities as a cornerstone for the success of their children purpose of this research is to find out how the school environment affects the learning outcomes of the seventh-grade student of mts al-hidayah perbaungan in moral education. The approach taken in this research is aquantitative approach through several stage of analysis namely validity testing reliability testing, normality testing, simple regression testing, and hypothesis testing, the results of the study indivate that the school environment with